Resistência de união à dentina de um sistema adesivo de frasco único : avaliação em 24 horas e seis meses de armazenamento - Manfroi, Fernanda Borguetti (2014)
The aim of this study was to evaluate the bond strength of Scotchbond Universal to dentin in both total-etch and self-etch applications after storage in water for 24 h and 6 months. The occlusal surface of 24 third molars was removed to obtain flat dentin surfaces, and the teeth were divided into four groups (n=6/grupo): G1 total-etch application of Scotchbond Universal; G2 self-etch application of Scotchbond Universal; G3 Scotchbond Multi Purpose (total-etch application control); G4 Clearfil SE Bond (self-etch application control). Following the adhesive application, a 6 mm height block of composite resin Z250 was built on the adhesive area. After storage in distilled water at 37ºC for 24 hours, the tooth/resin sets were cut parallel to the long axis of the tooth, in the x and y directions, with a section of about 0.8 mm2. Forty specimens were obtained for each group; 20 specimens were immediately submitted to microtensile bond strength test, and the others after storage in distilled water at 37o C for 6 months. The microtensile bond strength test was performed in an universal testing machine (EMIC-DL 2000) at 0.5 mm/min crosshead speed. The failures were observed in scanning electron microscopy (SEM). Additionally, two sets of each group were sectioned mesio-distal in the center of their crown with a diamond blade. The surfaces were polished by wet sanding with 400, 600 and 1200-grit silicon carbide abrasive paper, followed by polishing with 6, 3, 1 and ¼ m diamond paste. The samples were demineralized, deproteinized, dried, metalized and observed on a scanning electron microscope at 1.500x. The bond strength means (MPa) obtained were the following: 24 h G1 (39.37); G2 (31.02); G3 (35.09); G4 (35.84); 6 months G1 (36.99); G2 (40.58); G3 (32.44); G4 (41.75). According to two-way ANOVA, there was no significance for adhesive system (p=0,110) and storage time (0,108), but the interaction of adhesive system and storage time was significant (p=0.015). At 24 h, there was no statistical difference in bond strength between the adhesive systems (p>0,05). At 6 months, there was statistical difference between the adhesive systems (p<0.05). Clearfil SE Bond obtained the higher bond strength mean, not differing statistically from self-etch application of Scotchbond Universal. Total-etch application of Scotchbond Universal did not differ statistically from Scotchbond Multi Purpose. Most of failures were mixed in both periods of evaluation. The SEM images of the adhesive interface of Scotchbond Universal total-etch application and Scotchbond Multi Purpose showed thicker hybrid layers and more resin tags in comparison with Scotchbond Universal self-etch application and Clearfil SE Bond. It was concluded that the simplification of Scotchbond Universal in one bottle did not decrease the bond strength of this adhesive to dentin during 6 months of storage.